Comments on "Remarks on statistical errors in equivalent width" by K. Vollmann & T. Eversberg. Issue 1 (8th February 2018) - Netzel, C.
Abstract : Both Chalabaev & Maillard and Vollmann & Eversberg proposed calculation methods for the statistical error of the equivalent width. Both methods can lead to very different error bars. Here we present a straightforward expression for normalized spectra, which makes use of only standard commands of IRAF and favors the first method.